Two new species in the genus Atractides Koch, 1837 (Acari: Hydrachnidiae: Hygrobatidae), with the first descriptions of the female of two species from China - Yu-Hao Zhang; Hai-Tao Li; Zhan-Yu Hu; Jian-Jun Guo (European Journal of Taxonomy)
In this paper, two new species of Acari are described, i.e., Atractides (Atractides) cardiacus Zhang & Guo sp. nov. and Atractides (Atractides) fodingensis Zhang & Guo sp. nov. Moreover, the females of Atractides (Atractides) bitergumus Zhang & Guo, 2023 and Atractides (Tympanomegapus) tergumus Zhang & Guo, 2023 from Hainan Province and Guizhou Province of Oriental Region in China are described and illustrated for the first time.